2022
DOI: 10.3390/fermentation8010029
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Probiotic Properties of Lactic Acid Bacteria

Abstract: Oxidative stress, which can cause imbalance in the body by damaging cells and tissues, arises from the immoderate production of reactive oxygen species (ROS)/reactive nitrogen species (RNS). Therefore, external supplements having antioxidant activity are required for reducing oxidative stress. In our study, we investigated DPPH and ABTS radical scavenging ability, and the inhibition effect on the nitric oxide (NO) production of 15 food-derived bacterial strains in LPS-activated RAW264.7 cells. Among these LAB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…All LAB has DPPH and ABTS radical scavenging activity. Among them, MG5020 had the highest radical scavenging activity, as reported by Kim et al (2022).…”
Section: Resultsmentioning
confidence: 66%
“…All LAB has DPPH and ABTS radical scavenging activity. Among them, MG5020 had the highest radical scavenging activity, as reported by Kim et al (2022).…”
Section: Resultsmentioning
confidence: 66%
“…Another in vivo study reported clinical and animal model validation that a mixture of Lactobacillus and Bifidobacterium could significantly lower postoperative inflammation, enhance immunity, resume gut microbiota composition, and promote postoperative recovery [ 47 ]. According to previous studies, paraprobiotic bacterial strains including B. bifdum MG731, L. casei MG311, L. rhamnosus MG316, S. thermophilus MG5140, etc., had no cytotoxic to RAW264.7 cells, and especially B. bifdum MG731, which had the highest SCFA content among 17 bacterial strains, has high antioxidant activity and anti-inflammatory effects, showing the potential of functional paraprobiotics [ 48 , 49 ]. We speculated that the anti-tumor effects of heat-killed MG731 exhibit gastric cancer growth inhibitory effects via molecules involved in SCFAs, lipoteichoic acid, mannoprotein, and fimbriae.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence of probiotics to HT-29 colorectal cells was analyzed according to the protocol reported in a previous study [20]. Briefly, 1 mL of 1 × 10 6 HT-29 colorectal cells were grown in 12-well plates at 37 • C in an atmosphere containing 5% CO 2 until a cell monolayer was formed.…”
Section: Adherence To Ht-29 Colorectal Cellsmentioning
confidence: 99%